Analysis of social media in Karelia - Soyunen, Maxim (HAAGA-HELIA ammattikorkeakoulu, 2013)
Author Maxim Soyunen Group or year of entry 2009 Title of report Analysis of Social Media in Karelia Number of report pages and attachment pages 46+1 Teacher(s) or supervisor(s) Suvi Kalela, Mervi Riikonen This study is an attempt to raise awareness of the theories and practices, which shape the digital landscape of the world and Russia in particular, as well as of the multiple resources i.e. social platforms and tools that individuals and businesses use on equal terms to generate content and interaction on the web. The research is aimed at answering the questions who and how is using social media in Karelia, which SM channels are most popular in Karelia and what role does it play in the life of a Karelian. The theoretic part of the thesis reviews several important perspectives of SM, as a marketing and interaction solution. One of them is Dave Evans, who explains SM’s empowering effect on the social feedback cycle and consequentially the purchase funnel. Lon Safko, author of the Social Media and Fusion Marketing Bible,Brian Solis, Fred Cavazza and other contributors, movers and thinkers. This thesis includes an overview of Russian social media environment, statistics and facts about presence of individuals and brands in Russian and Karelian social web and findings from qualitative interviews with Karelians over their online presence – most commonly on three to four well known networks, out of which Vkontakte.ru is the only Russian network by origin. Results have shown that Karelians, inhabitants of the third most connected Russian republic, eagerly consume globally and locally created content and reflect on it in consistency with the evolving, already one billion worth of human attention, digital flow. Keywords Karelia, Social Media, Fusion Marketing, , Social Feedback Cycle